Celiac disease prevalence in patients with iron deficiency anemia of obscure origin - Derya UÇARDAĞ; Sefa GÜLİTER and Özcan ÇENELİ and Fahri YAKARYILMAZ and Pınar ATASOY and Osman ÇAĞLAYAN (Turkish Journal of Gastroenterology, 2019)
-